Water to the angels : William Mulholland, his monumental aqueduct, and the rise of Los Angeles - Standiford, Les (Ecco, 2015)
Documents the story of William Mulholland's Los Angeles aqueduct, the largest public water project ever built, describing how it transformed a small desert city into a modern metropolis.